LOS POBRES ANTE LA JUSTICIA: DISCURSOS, PRÁCTICAS Y ESTRATEGIAS DE SUBSISTENCIA EN BUENOS AIRES (1785-1821) - Lucas Rebagliati (Boletín del Instituto de Historia Argentina y Americana Dr. Emilio Ravignani, 2013)
This work analyzes different kinds of poverty in the city of Buenos Aires during the period 1785-1821. For that, a social profile of those who appealed to the Real Audiencia –thereafter Corte de Apelaciones– to be declared pobres solemnes in order to litigate without charges, will be drawn. Through a prosopographical approach, different variables such as gender, “race”, marital status and occupation will be considered, and how they affected the lives of the petitioners, distinguishing the most usual causes of social decline. Specific life stories will be also analyzed to enlighten general patterns, and to find out the strategies that individuals coming from various social sectors displayed to alleviate their hardships and uphold their rights.